2009
DOI: 10.1097/mao.0b013e3181b76b08
|View full text |Cite
|
Sign up to set email alerts
|

Microdrill, CO2-Laser, and Piezoelectric Stapedotomy

Abstract: The use of the CO2 laser seems associated with the best functional results, although on a statistical basis, they do not differ significantly from that obtained with the standard MD platinotomy. The PZS stapedotomy is effective from a surgical point of view for most patients. However, it is associated with a slight but significant deterioration of BC at high frequency and at higher vertigo rate. More basic validation of the stimulation parameters is necessary for safe use of this new technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 10 publications
3
29
0
2
Order By: Relevance
“…The long-term follow-up (on average 45 months) confirmed the stability of the hearing improvement. In the postoperative assessment, average values of ACPTA for 0.25 and 0.5 kHz are substantially lower compared to those at 2 and 4 kHz, which results in higher ABG closure at lower frequencies, as already reported in analogous studies [2]. Less residual ABG at low frequencies represents unanimously a successful marker for functional outcome.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The long-term follow-up (on average 45 months) confirmed the stability of the hearing improvement. In the postoperative assessment, average values of ACPTA for 0.25 and 0.5 kHz are substantially lower compared to those at 2 and 4 kHz, which results in higher ABG closure at lower frequencies, as already reported in analogous studies [2]. Less residual ABG at low frequencies represents unanimously a successful marker for functional outcome.…”
Section: Discussionmentioning
confidence: 60%
“…Several laser systems have been employed for stapes surgery in order to obtain higher functional results compared to common traditional devices such as manual perforator and/or ultralight microdrill [2,3]. Over the years, standardized and reproducible outcomes have been achieved, together with progressive reduction of the rates of intraoperative labyrinthine trauma, due to footplate manipulation.…”
Section: Introductionmentioning
confidence: 99%
“…In average, the operation time reduced about onethird and the completion rate of stapes surgery increased about one-fifth after implementing diode laser in our department. Several studies have also demonstrated that regardless of devices used to create the stapedotomy (manual perforator, micro-drill or lasers) no significant difference in either post-operative ABG closure or postoperative sensorineural hearing loss can be found [4][5][6][7][8][9][10]. Some studies have shown that micro-drill is superior to manual perforator [14] and CO2-laser is superior to potassium-titanyl-phosphate (KTP) laser [15], but these improvements were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most remarkable technical innovations was the introduction of lasers in stapes surgery already three decades ago [2,3]. However, several earlier and latter studies have shown no significant differences between laser-assisted, micro-drill and manual microsurgical stapedoplasty with regard to hearing outcome [4][5][6][7][8][9][10]. Instead of better hearing outcome, the micro-drill and/or laser appears to be very helpful to provide greater accuracy during precise manipulations and thereby reduce surgical trauma, which is important advantages regarding patients' safety compared to handheld instruments [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Der Vergleich von Hörergebnissen nach Anwendung des Er:YAG-, KTP-und CO 2 -Lasers zeigte die größte Schallleitungsverbesserung nach CO 2 -Laser-Stapedotomien [33,53]. Auch der Vergleich des CO 2 -Lasers mit konventionellen Methoden der Stapedotomie (Mikrobohrer, Piezoelektrik) verlief zugunsten des CO 2 -Lasers [8]. Der Vergleich zwischen dem Argon-und dem CO 2 -Laser ergab keinen signifikanten Unterschied [6].…”
Section: Literaturvergleich Der Ergebnisse Nach Stapedotomieunclassified